(untitled) (DAPesquisa, 2020)
This article reports the experience of a pedagogical practice focused on the design of textile surfaces. The practice included the creation of textile patterns and was based on the transposition of socio-cultural aspects of certain countries for the materialization of textile samples. Held in the first semester of the 2019 school year, the practice involved students in the Textile Patterns discipline, taught by Professor Dulce Maria Holanda Maciel. Methodologically, this report fits as descriptive, qualitative, bibliographic and field research, since its data collection involved bibliographic survey and clippings of the works produced by the students, followed by narrative and interpretative analysis. It is inferred that the hypothesis outlined by the professor about future designers being able to articulate socio-cultural aspects as a source of research and inspiration for the creation of new textile patterns was corroborated through the investigated literature and the reported experience.